Surface modification of porous titanium with rice husk as space holder - Xinsheng Wang; Junjian Hou; Yanpei Liu (Results in Physics, 2018)
Porous titanium was characterized after its surface modification by acid and alkali solution immersion. The results show that the acid surface treatment caused the emergence of flocculent sodium titanate and induced apatite formation. The surface modification of porous titanium promotes biological activation, and the application of porous titanium is also improved as an implant material because of the existence of C and Si. Keywords: Porous titanium, Surface modification, Microstructure, XPS